Fetal ventricular shortening fraction in hydrops fetalis - Theera Tongsong (2018)
Objective: To estimate fetal ventricular shortening fraction, representing cardiac contractility, derived from cardiospatiotemporal image correlation with M-mode display "STIC-M" in fetuses with hydrops fetalis secondary to high-output (fetal anemia) and low-output causes (congenital heart defects). Methods: A cross-sectional study was conducted in normal fetuses (group 1), fetuses with hemoglobin Bart's disease with (group 2) and without (group 3) hydrops fetalis, and those with hydrops fetalis resulting from cardiac defects (group 4). Volume data sets of cardiospatiotemporal image correlations were acquired for each group for subsequent offline analysis with cardiospatiotemporal image correlation with M-mode display. Group 1 data were used to construct reference ranges of left and right ventricular shortening fraction for assessment of fetuses in the remaining groups. Results: A total of 606 measurements, 15-35 per week, were performed in normal fetuses to construct reference ranges as well as Z-scores of left and right ventricular shortening fraction. Both parameters were decreased with increasing gestation with weak correlation (r=0.141, P<.001 and r=0.055, P<.001, respectively). Shortening fraction did not significantly change among 111 fetuses with hemoglobin Bart's disease with and without hydrops. However, left and right ventricular shortening fraction were significantly decreased (mean Z-scores 5 standard deviations and 8 standard deviations below the mean, respectively) in 21 hydropic fetuses as a result of congenital heart defects (P<.001). Conclusion: Fetuses with hydrops fetalis secondary to cardiac defects and anemia have a different pattern of shortening fraction. Hydrops fetalis resulting from cardiac defect is primarily caused by cardiac decompensation; whereas in fetal anemia, it is probably caused by hypervolemia with cardiac decompensation occurring when the cardiac compensatory mechanism is exhausted. © 2010 by The American College of Obstetricians and Gynecologists. Published by Lippincott Williams & Wilkins.